Schwannoma of the common peroneal nerve – a rare incidence - Tan JA,; Levin KB,; Shaharuddin Abd. Rhani,; Hisam A, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Schwannomas are benign tumours arising from neurilemmal cells which forms the myelin sheath of peripheral nerves. It usually occurs in the head, but may be found in the brachial plexus and sciatic nerve. Common peroneal nerve schwannoma are rare. We report a case of a middle age gentleman who presented with pain and swelling over the right popliteal fossa with associated right radicular pain of the anterolateral leg and weakness of ankle dorsiflexion. Examination revealed a 3x2 cm lump behind the posterolateral aspect of the right knee with positiveTinel’s sign upon tapping of the lump, sensory deficit over the anterolateral aspect of the leg and the ankle dorsiflexors had a muscle power of grade 3. Magnetic resonance imaging (MRI) of the right leg revealed a well circumscribed, oval lesion located along the pathway of the common peroneal nerve homogenously hypointense on T1-weighted images and heterogeneously hyperintense on T2 weighted images compared to the muscles. The lesion was not surpressed on fat suppression sequences. Intra-operatively, we noted that the schwannoma was in continuity with the common peroneal nerve. The patient underwent excision of the schwannoma. Post operatively, the pain reduced remarkably but patient suffers from numbness and right foot drop as a complication of the tumour. This case highlights the rarity of common peroneal nerve schwannoma which presents with neuropathic symptoms complicated with right foot drop.